Survey sampling: A necessary journey in the prediction world - Jan F. Bjørnstad (Statistics Norway, Research Department, 2010)
The design-approach is evaluated, using a likelihood approach to survey sampling. It is argued that a model-based approach is unavoidable from a scientific point of view. Estimating population quantities can then be regarded as a prediction problem. Predictive likelihood methods are considered in various cases, and evaluated by properties of related confidence intervals and asymptotic consistency.
Keywords: C10; 330; likelihood; predictive likelihood; asymptotic consistency.